Audit committee and the quality of financial reporting information - evidence in the new organisational structure of Vietnamese listed companies - Doan Minh Duc, Le; Loi, Huynh; Quoc Viet, Phung (Edelweiss Applied Science and Technology, 2024)
The Audit Committee (AC) is a new part of organisational structure of a joint-stock company (JSCs), which has just been legislated in Vietnam since 2021. The AC aims to supervise activities to enhance the truthfulness and fairness of financial reporting information. The article aims to analyze and evaluate the actual effectiveness of the AC in improving the quality of financial statement information. The secondary data including 255 observations from listed companies that have established AC. We carried out analysis and forecast using the binary logistic model. The results show that the AC has played a primary role to improve the quality of financial statement information.